Aksjologiczne spojrzenie na instytucję tymczasowego aresztowania w postępowaniu karnym - Wielec, Marcin (Kwartalnik Prawa Publicznego, 2016)
In the literature of the subject, the institution of temporary detention is analyzed frequently and in detail. Nevertheless, these analyzes focus on strictly criminal procedural issues such as interpreting the grounds for detention, limiting its application, or on the general issue of preventive measures to which the temporary detention obviously belongs. Provisional detention can also be analyzed from the axiological point of view, which means that one can study the institution through the prism of generally known values associated with the juridical area. It may be interesting to analyze the temporary arrest from the point of view of axiological positions, which are determined by research determinants, not directly from criminal proceedings, which is infrequent in literature where the dogmatic-legal analysis is more prevalent.